DISPARITAS PUTUSAN HAKIM DALAM PEMBERIAN HADHANAH PADA IBU MURTAD PERSPEKTIF MAQĀSĪD AL-SYARĪAH (Studi Putusan Nomor 2800/Pdt.G/2018/PA.Jb dan Putusan Nomor 0679/Pdt.G/2020/PA.Klt) - Husniati, Siti Ida; Kamarusdiana, Kamarusdiana; Yassardin, Yassardin (Journal of Islamic Studies and Humanities, 2024)
Purpose of this Study Researchers will examine the provision of child custody due to mothers who have apostatized. from 2 different religious court decisions, both of which have different considerations and rulings. This research is a normative juridical research using statute approach and case approach. Primary data sources are Decision Number 2800/Pdt.G/2018/PA.JB and Decision Number 0679/Pdt.G/2020/PA.Klt, Law Number 1 of 1974 concerning marriage, and the Compilation of Islamic Law (KHI). Secondary data sources are books, journals, articles and related literature. Based on the results of this study, it was found that a mother who apostatized could also not get custody of the child. his is in accordance with the book, hadith, fiqh rules, Supreme Court Jurisprudence No. 210/K/AG/1996, 110 K/Ag/2007, and viewed from the perspective of Maqasid al-Syari'ah can be seen in giving custody of the child to his father solely to maintain the element of hifz ad-din of the child. In the aspect of hifz ad-din, it is included in the ad-dharuriyat needs because the granting of child custody to an apostate mother can threaten the child's religion, such as the transition of the child's religion. In giving custody of children to their mothers, it is included in the needs of al-hājiyāt, namely hifz an-nafs.